ALL-OPTICAL HYSTERESIS SWITCHING USING MOBIUS CONFIGURATION MICRORING RESONATOR CIRCUIT - Ahmad Fakhrurrazi Ahmad Noorden; Azam Mohamad; Mahdi Bahadoran; Kashif Chaudhary; M. S. Aziz; Muhammad Arif Jalil; Jalil Ali; Preecha Yupapin (My University, 2015)
The novel twisted ring resonator called add-drop Mobius microring resonator is introduced and modelled with the analytical solution of transfer matrix methods for the generation of optical bistability. Simulated results show that, the add-drop Mobius configuration provides greater phase shift due to the longer length of propagation per roundtrip than add-drop filter configuration. In add-drop Mobius system, drop port generated the optical bistable hysteresis loop with 19.25 mW output switching power and through port generated lower switching power as 5.55 mW. The drop port of the system is found as the suitable port for the operating the all-optical hysteresis switching.
Keywords: Bistability; Optical Bistability; Port (circuit theory); Hysteresis; Photonic and Optical Devices